(untitled) (Altre Modernità, 2020)
A language is never practiced in a uniform way from one region to another within the same community, or even from a linguistic community to another. Thus, the French practiced in Haiti that Pompilus (1961), Govain (2008, 2009, 2013), Saint-Fort (2007), Fattier (2010) called Haitian French (HF) is a variety of French speaking specific to Haiti and different in many ways from other varieties of French in the ‘Francophonie’. HF is therefore not identical from all points of view with the other varieties of French speaking but there exists between all these varieties an invariance zone which guarantees intercomprehension. The French language, arrived in the place that will become Haiti today, during the first half of the seventeenth century, will evolve differently from the varieties of French that will develop in various places: time, space and generations print their mark on linguistic practices. The specificities of HF come from the endogenous norms that are facilitated by various local experiences, Haitian Creole, Anglo-American and Spanish. They manifest themselves in particular at the lexico-semantic aspect, but also phonological, and to a lesser extent morphosyntactical. Lexico-semantic differences between the HF and common French (CF) give rise to "false-friends" that can lead to problems of interpretation between the speakers of these varieties. This contribution proposes a brief description of the HF from the productions of 1st year university students.